Sumatriptan decreases food intake and increases plasma growth hormone in healthy women. - Boeles, S; Williams, C; Campling, G; Goodall, E; Cowen, P (1997)
We studied the effect of the 5-HT1B/ID receptor agonist sumatriptan (6 mg s.c.) on plasma growth hormone and prolactin and food intake in 15 healthy female subjects using a double-blind, placebo-controlled, cross-over design. Sumatriptan significantly elevated plasma growth hormone but did not alter plasma prolactin. Sumatriptan also significantly lowered total food intake in a buffet meal, particularly decreasing the intake of fat. Our results indicate that 5-HT1B/ID receptors may be involved in the regulation of food intake in humans. In addition, while activation of 5-HT1B/ID receptors stimulates growth hormone release in both men and women, sumatriptan lowers plasma prolactin only in men, suggesting sex differences in the 5-HT regulation of prolactin release.